HISTORY OF SOCIAL FUNCTION FORMATION IN THE ANCIENT RUS STATE - Voronkov, Kirilvl Ilyich; Romanovskaya, Vera Borisovna; Silantyeva, Victoria Alexandrovna; Fedyushkina, Arina Igorevna; Bondarenko, Alexander Viktorovich (Revista Notas Históricas y Geográficas, 2021)
The present article deals with the formation of the social function of the state in the context of ancient Rus state. The essence of the social function was determined by the level of economic development, and the nature of the state that had developed during the period from 9th to the first third of the 13th century. The authors provided a historical and legal review of the social legislation development of the ancient Rus state starting from the period of the first Russian princes' rule. It is established that the main principle of the social policy of the ancient Rus state was the practice of "Christian merciful attitude". It is proved that the peculiarity of the implementation of the social function of the ancient Rus state was the delegation of certain powers for social support of the population by the state to the Orthodox Church. The article analyzes the activities of Church institutions in promoting charity.